Pelatihan Pemanfaatan Teknologi Informasi untuk Guru Sekolah Dasar dalam Pembelajaran di SD Negeri 101736 Medan Krio - Siti Nurhabibah Hutagalung; Melda Panjaitan (Cattleya Darmaya Fortuna, 2026)
This community service program aims to enhance the competence of elementary school teachers in utilizing information technology in the learning process. In the digital era, teachers are required not only to master conventional teaching methods but also to be able to integrate technology as a learning medium in order to create more interactive, creative, and up-to-date learning experiences. The program methods include coordination with schools, digital literacy workshops, training on office applications (Microsoft Word, Excel, and PowerPoint), training on digital learning media (Canva and Google Classroom), hands-on practice mentoring, and evaluation of teachers’ skills. This program is designed to involve elementary school teachers as the main participants. The expected outcomes of this program are an improvement in teachers’ digital literacy, the ability to create technology-based learning media, and the effective use of online learning applications. Thus, this activity is expected to support the implementation of more modern, innovative, and effective learning in elementary schools.